Features of the formation of motivation for physical education classes among schoolchildren - Sobyanin, F.I.; Ten, A.A.; Nikulin, I.N.; Kolesnikov, N.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the main features of the formation of motivation among secondary school students to engage in regular physical education classes. Methods and structure of the study. A questionnaire survey was conducted among secondary school children in the Belgorod Oblast. An excerpt from the study is presented using the example of grades 5-8 (n=320). The results after initial processing are given as percentages. Results and conclusions. Data has been obtained on negative and positive trends, factors influencing the motivation of secondary school students to participate regularly in physical education, and factors determining its specificity. The physical education motivation of schoolchildren is characterised in terms of its internal and external components. The dominant positive motivation of students to participate in physical education is confirmed by their high regularity of attendance at physical education classes and sports clubs outside of school, their positive attitude towards teachers, coaches and their pedagogical efforts, and the support of parents for the physical and sports activities of schoolchildren. The negative side of children's motivation is expressed in an insufficient understanding of the personal and social significance of physical education, a lack of independent activity among schoolchildren in learning about the values of physical education, and the absence of physical education in students' plans for their future lives.